Leveraging the Critical Incident Technique (CIT) in Identifying Effective Team Learning Thematic Variables - Constance Carpenter (Adult Education Research Conference, 2018)
The research explores the reconceptualization of the Critical Incident Technique (CIT) as a systematic method to identify and to deconstruct team learning thematic variables associated with effective performance.
Keywords: critical incident technique; team learning; high performing teams